THE QUALITY OF PUBLIC SERVICES AND ITS INFLUENCE ON THE PUBLIC SATISFACTION INDEX AT SUKOHARJO DISTRICT OFFICE, PRINGSEWU REGENCY IN 2024 - Setyaningsih, Leni; Virgawenda, Tina Miniawati Barusman; Barusman, Andala Rama Putra (Journal of Management, Business and Social Sciences, 2024)
This study aims to investigate the influence of public service quality on the Public Satisfaction Index (IKM) at the Sukoharjo District Office, Pringsewu Regency, by employing a quantitative research method with a population consisting of 73 hamlet heads. Data analysis was carried out using the t-test, F-test, and multiple linear regression through SPSS software. The findings reveal that the tangible and reliability variables do not have a significant impact on the Public Satisfaction Index, as indicated by t-values smaller than the t-table. In contrast, the responsiveness variable shows a significant effect with a t-value of 1.995 exceeding the t-table, while assurance also demonstrates a significant relationship with a t-value of 2.076 and a significance level of 0.042, which is below the threshold of 0.05. Similarly, empathy exerts a significant effect with a t-value of 2.600 and a significance level of 0.011, both confirming its influence on public satisfaction. Descriptive statistical analysis further highlights that the highest indicator for tangibles is the availability of representative office buildings (4.96), for reliability is the provision of free services (4.33), for responsiveness is the delivery of well-responded services (4.73), for assurance is the equal treatment in service provision, and for empathy is the implementation of polite and friendly service, which achieved the highest average score (4.23). These results suggest that while physical facilities and reliability contribute less significantly, dimensions such as responsiveness, assurance, and empathy play a more crucial role in shaping public satisfaction with government services at the district level.